Teenagers of Kyzyl (Republic of Tuva) in the online space - Evert, Lydia S.; Seren-ool, Sayana S.; Sat, Diana A. (The New Research of Tuva, 2023)
The study is dedicated to investigating the prevalence of various internet usage patterns, including adaptive (API), non-adaptive (NPI), and pathological (PPI) behaviors, as well as examining the characteristics of internet content consumed by adolescents in Tuva, considering their diverse age, gender, and ethnic backgrounds. The research findings are based on the analysis of offline testing results conducted among adolescents in Kyzyl, serving as the empirical foundation for this article. The surveys were carried out through a random sampling method from December 2020 to May 2021, involving 1659 participants who completed three psychometric instruments (CIAS scale), along with questionnaires for verifying dependence on social networks and gaming addiction.A comparative analysis of indicators was performed among groups differing in terms of age, gender, and ethnic background (Tuvans, Russians). The study revealed the prevalence of internet-dependent behavior and the specific structure of internet activity content consumed within the comparison groups. Adaptive internet usage (API) was observed in 34.3% of all participants, non-adaptive internet usage (NPI) in 51.3%, and pathological internet usage (PPI) or internet addiction in 14.4% of adolescents.Particular attention was paid to examining the impact of ethnic background on online behavior among adolescents. The study found a higher frequency of maladaptive (NPI and PPI) online behaviors among Tuvan adolescents. Gender differences were also noted, including a higher incidence of PPI among Tuvan girls compared to Tuvan boys. NPI was more frequently recorded among Tuvan adolescents (both boys and girls). Regarding the analyzed indicators and their correlation with age, significant age-related differences were not identified across all types of online behavior, except for younger Tuvan adolescents, where NPI was more prevalent.The analysis of consumed internet content revealed dependency on social networks in 13.9% of adolescents, gaming addiction in 5.2%, mixed addiction in 9.2%, and undifferentiated addiction in 5.4% (with no significant ethnic differences observed). Gender differences were identified in the prevalence of various types of internet addiction: gaming addiction was higher among Tuvan boys, undifferentiated addiction was more common among girls, and dependency on social networks was more prevalent among girls, both Tuvan and Russian. Among boys, this dependency was higher among Tuvan boys compared to their Russian counterparts.
Keywords: adolescent; Tuva; Kyzyl; Internet; online behavior; addiction; consumed content; Tuvans; Russians